Habituation or Normalization? Experiential and Respiratory Recovery From Voluntary Hyperventilation in Treated Versus Untreated Patients With Panic Disorder. Issue 1 (January 2021) - Tunnell, Natalie C.; Ritz, Thomas; Wilhelm, Frank H.; Roth, Walton T.; Meuret, Alicia E.
Abstract: Psychophysiological theories postulate respiratory dysregulation as a mechanism contributing to panic disorder (PD). Additionally, symptomatic and respiratory recovery from voluntary hyperventilation (HVT-recovery) have been shown to lag in PD and it is unclear if HVT-recovery normalizes with treatment. Thirty-seven panic disorder patients were randomized to hypoventilation therapy (TX, n = 20) or waitlist control (WL, n = 17) (Meuret et al., 2008). In a secondary analysis, their HVT-recovery was analyzed at pre- and post-TX/WL, compared to 29 healthy controls (HC). HVT included three phases: 5-min baseline, 3-min hyperventilation, and 8-min recovery. HVT-elicited symptom severity and anxiety were rated following each phase, and end-tidal PCO2 and respiratory rate (RR) were recorded throughout. Treatment, compared to WL, was highly effective in reducing PD pathology (d = 2.21, Meuret et al., 2008). At pre-TX/WL, PD demonstrated delayed HVT-recovery PCO2 and higher RR. Treated patients demonstrated normalization of HVT-recovery for PCO2 and RR; however, improvements of HVT-recovery for symptom severity and anxiety did not differ between TX and WL. Results replicate pretreatment HVT respiratory recovery abnormalities in PD and further demonstrate normalization, comparable to HC, following successful treatment. The results provide support for respiratory dysregulation as a feature of PD and demonstrate the utility of HVT respiratory recovery as treatment outcome measure for respiration-based PD therapy. Highlights: Panic patients show slower respiratory recovery to hyperventilation before therapy Respiratory therapy resulted in normalization of recovery PCO2 and respiratory rate Improvement in symptom severity and anxiety didn't differ among treated and waitlist Waitlist improvements suggest experiential habituation without physiological change